2017 25th European Signal Processing Conference (EUSIPCO) 2017
DOI: 10.23919/eusipco.2017.8081663
|View full text |Cite
|
Sign up to set email alerts
|

Using deep learning to detect price change indications in financial markets

Abstract: Abstract-Forecasting financial time-series has long been among the most challenging problems in financial market analysis. In order to recognize the correct circumstances to enter or exit the markets investors usually employ statistical models (or even simple qualitative methods). However, the inherently noisy and stochastic nature of markets severely limits the forecasting accuracy of the used models. The introduction of electronic trading and the availability of large amounts of data allow for developing nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 11 publications
0
80
0
Order By: Relevance
“…Due to the erratic, noisy nature of stock price movement, many deep neural networks were proposed within a complex forecasting pipeline. For example, in high-frequency LOB data, the authors proposed to normalize the LOB states by the prior date's statistics before feeding them to a CNN [47] or an LSTM network [48]. A more elaborate pipeline consisting of multiresolution wavelet transform to filter the noisy input series, stacked Auto-Encoder to extract high-level representation of each stock index and an LSTM network to predict future prices was recently proposed in [54].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the erratic, noisy nature of stock price movement, many deep neural networks were proposed within a complex forecasting pipeline. For example, in high-frequency LOB data, the authors proposed to normalize the LOB states by the prior date's statistics before feeding them to a CNN [47] or an LSTM network [48]. A more elaborate pipeline consisting of multiresolution wavelet transform to filter the noisy input series, stacked Auto-Encoder to extract high-level representation of each stock index and an LSTM network to predict future prices was recently proposed in [54].…”
Section: Related Workmentioning
confidence: 99%
“…In recent work [46], we have showed that a linear multivariate regression model could outperform other competing shallow architectures that do not take into account the temporal nature of HFT data. While performing reasonably well compared to other shallow architectures, the learning model in [46] has certain short-comings in practice: the analytical solution is computed based on the entire dataset prohibiting its application in an online learning scenario; with large amount of data, this model clearly underfits the underlying generating process with performance inferior to other models based on deep architectures [47], [48]. In this work, we propose a neural network layer which incorporates the idea of bilinear projection in order to learn two separate dependencies for the two modes of multivariate time-series data.…”
Section: Introductionmentioning
confidence: 99%
“…Makinen et al [37] predict price jumps with the use of LSTM, where the input data is based on LOB data. A similar work, in terms of the neural model, is conducted in [53] in order to forecast LOB's mid-price.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Forecasting time series is an increasingly important topic, with several applications in various domains [1], [5], [13], [15], [16], [19], [23], [34]. Many of these tasks are nowadays tackled using powerful deep learning (DL) models [6], [8], [14], [29], [31], which often lead to state-of-the-art results outperforming the previously used methods. However, applying deep learning models to time series is challenging due to the non-stationary and multimodal nature of the data.…”
Section: Introductionmentioning
confidence: 99%